Pengaruh Pemberian Pupuk Kompos Eceng Gondok Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) pada Berbagai Media Tanam - Imelda Amri; Eny Fuskhah; Sutarno Sutarno (JURNAL AGROPLASMA, 2023)
The reasearch aimed to examine the effect of water hyacinth compost fertilizer dosage on the growth and yield of pakcoy (Brassica rapa L.) on various planting media. The research was conducted from February 2022 to April 2022 at the Green House of the Food Plant Protection and Horticulture Agency of Central Java Province and the Laboratory of Plant Ecology and Production, Faculty of Animal Husbandry and Agriculture, Diponegoro University, Semarang. The research design used was a 4 x 3 factorial completely randomized design (CRD) with 3 replications. The first factor (P) consisted of 4 levels of water hyacinth compost dosage, namely P0 = control, P1 = 25 tons/ha, P2 = 30 tons/ha and P3 = 35 tons/ha. The second factor (K) consists of several types of planting media, namely K0 = soil, K1 = soil + husk charcoal (3:1) and K2 = soil + cocopeat (3:1). Parameters observed were plant height, number of leaves, fresh weight and dry weight of plants, root length, root weight, total chlorophyll and harvest index. The data obtained were tested using the Analysis of Variance (ANOVA) and the results that significantly affected the observed parameters were then further tested using Duncan’s Multiple Range Test (DMRT) at the level 5%.The results showed that the dose of 25 tons of water hyacinth compost fertilizer with soil planting media can increase the growth and yield of pakcoy (Brassica rapa L.) the highest and most efficiently. Keywords: dose, compost fertilizer, pakcoy